Locally differentially private continuous location sharing with randomized response - Xingxing Xiong; Shubo Liu; Dan Li; Jun Wang; Xiaoguang Niu (International Journal of Distributed Sensor Networks)
With the growing popularity of fifth-generation-enabled Internet of Things devices with localization capabilities, as well as on-building fifth-generation mobile network, location privacy has been giving rise to more frequent and extensive privacy concerns. To continuously enjoy services of location-based applications, one needs to share his or her location information to the corresponding service providers. However, these continuously shared location information will give rise to significant privacy issues due to the temporal correlation between locations. In order to solve this, we consider applying practical local differential privacy to private continuous location sharing. First, we introduce a novel definition of ( ε , δ ) -local differential privacy to capture the temporal correlations between locations. Second, we present a generalized randomized response mechanism to achieve ( ε , δ ) -local differential privacy for location privacy preservation, which obtains the upper bound of error, and serve it as the basic building block to design a unified private continuous location sharing framework with an untrusted server. Finally, we conduct experiments on the real-world Geolife dataset to evaluate our framework. The results show that generalized randomized response significantly outperforms planar isotropic mechanism in the context of utility.